Pixel Intensity-Based Contrast Algorithm (PICA) for Image Edges Extraction (IEE) - Al-Ghaili A.M.; Kasim H.; Al-Hada N.M.; Othman M.; Saleh M.A.; Jihua W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Edge detection; Extraction; Medical imaging; Pixels; Code complexity; Complex background; Computation time; Open sources; Pixel intensities; Real-time application; Single images; Video motion; Image enhancement